2023
DOI: 10.1111/cns.14217
|View full text |Cite
|
Sign up to set email alerts
|

Advances in research on immune escape mechanism of glioma

Abstract: Background Glioma is the most common primary intracranial malignancy in clinical practice, and in particular, IDH‐wildtype glioblastoma has the worst prognosis. In recent years, surgical resection combined with simultaneous radiotherapy and immune checkpoint inhibitors has made some progress, but the efficacy is still not satisfactory, which may be related to the low immunogenicity of glioma cells and the tumor immunosuppressive microenvironment. Methods A comprehensive review of relevant literature was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 93 publications
0
4
0
Order By: Relevance
“…Based on the presented subsidiary analysis of immune cellular components and myeloid-associated genes, it can be suggested that groups of patients having unfavorable DFS, especially “Vec”-like “UTU” patients, are affected by more immunosuppressive GBM tumors. Evading immunosurveillance or immunotherapy resistance are major obstacles to GBM treatment ( Liu et al, 2021 ), and dynamic communication with the immune tumor microenvironment is inherent during GBM progression ( Arrieta et al, 2023 ; Guo and Wang, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the presented subsidiary analysis of immune cellular components and myeloid-associated genes, it can be suggested that groups of patients having unfavorable DFS, especially “Vec”-like “UTU” patients, are affected by more immunosuppressive GBM tumors. Evading immunosurveillance or immunotherapy resistance are major obstacles to GBM treatment ( Liu et al, 2021 ), and dynamic communication with the immune tumor microenvironment is inherent during GBM progression ( Arrieta et al, 2023 ; Guo and Wang, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…These findings are surprising given the fact that other groups reported that there is a connection between TG2 activity and the molecular events that regulate the mesenchymal transition in GBM cells [26,89], although we did not discriminate GBM subtypes in our analysis. Correlation analyses on the myeloid markers suggested that tumor-associated myeloid cells can cooperate with both lymphocytes and inflammatory cells to potentially induce chemoresistance, tumor inflammation and tumor-mediated immune evasion mechanisms involved in the glial tumor progression [90]. The correlation between gene expression and OS of gliomas were assessed by Kaplan-Meier analysis using public databases available on GEPIA2 portal.…”
Section: Discussionmentioning
confidence: 99%
“… 38 , 39 In addition, immunosuppression is a key aspect of escaping immune recognition which was also partly induced by low immunogenicity, antigenic modulation, and immune‐privileged site. 40 TAM played a vital role in immune escape in GBM through upregulating programmed death ligand 1(PD‐L1) expressed on GBM and activating programmed death 1(PD‐1) expressed on TAM. 40 , 41 , 42 A range of chemokine chemotactic factors, such as alkB homolog 5, C‐C motif chemokine ligand 2/5 (CCL2/5), chitinase‐3‐like protein 1 (CHI3L1), C‐X3‐C motif chemokine ligand 1 (CX3CL1), and C‐X‐C motif chemokine ligand 8 (CXCL8) expressed and secreted by GBM cells, induce intratumoral immune suppression via promoting TAM infiltration and immunosuppressive polarization.…”
Section: Mechanism Of Teftmentioning
confidence: 99%
“… 40 TAM played a vital role in immune escape in GBM through upregulating programmed death ligand 1(PD‐L1) expressed on GBM and activating programmed death 1(PD‐1) expressed on TAM. 40 , 41 , 42 A range of chemokine chemotactic factors, such as alkB homolog 5, C‐C motif chemokine ligand 2/5 (CCL2/5), chitinase‐3‐like protein 1 (CHI3L1), C‐X3‐C motif chemokine ligand 1 (CX3CL1), and C‐X‐C motif chemokine ligand 8 (CXCL8) expressed and secreted by GBM cells, induce intratumoral immune suppression via promoting TAM infiltration and immunosuppressive polarization. 39 , 43 Combination of TEFT and anti‐PD‐1 therapy induced antitumor immune response, 44 which may block the GBM immune evasion.…”
Section: Mechanism Of Teftmentioning
confidence: 99%